Multiple-Echo Suppression Modeling and Experimental Verification for Acoustic Transmission along Periodic Drillstring Using Dual Receivers - Li Cheng; Chang Jinfeng; Liu Zhao; Fan Shangchun (Shock and Vibration)
In the oil industry, the accompanied reverberation is a major constraint in the transmission rate and distance because the drillstring is a heterogeneous assembly. Based on the transient impulse responses in uplink and downlink channels, an improved simplified echo suppression model with two acoustic receivers is presented in consideration of position optimization of single acoustic receiver. Then the acoustic receiving characteristics of transmitted signals in a length-limited periodic drillstring channel are obtained in single- and dual-receiver modes. An additive downward white Gaussian noise is also introduced in the channel. Moreover, an experimental rig is established by using a rotatable electromagnetic vibration exciter and two piezoelectric accelerometers, which are spaced one-quarter wavelength apart along a 6.3-meter simulated periodic drillstring. The ASK-, FSK-, and PSK-modulated square-wave pulse sequences at a transmission rate of 200 bit/s are applied to the simulated drillstring at a rotation speed of 0, 80, and 140 r/min, respectively. The experimental results show that the dual-receiver mode can exhibit a significantly improved average error bit ratio, which is approximately 2.5 to 3 times lower than that of the single-receiver mode, especially under the conditions of higher rotation speeds.